Development of a novel method for measuring the interfacial bonding strength of laser cladding coatings. (April 2022) - Nie, M.H.; Zhang, S.; Wang, Z.Y.; Zhang, H.F.; Zhang, C.H.; Chen, H.T.
Highlights: A novel test method for measuring the normal bonding strength between the interface. The specially T-shaped sample and the related fixture are designed. The T-shaped specimens with different cross-sectional areas are analyze and compared. Comparative experiments show that the test method has excellent repeatability and effectiveness. Abstract: Interface bonding strength is a crucial factor that determines the final mechanical properties and performance of laser cladding coatings. Due to the metallurgical bonding caused by laser cladding, the traditional method of measuring normal interface bonding strength is difficult to use. The present paper proposes a self-designed T-shaped sample and related fixtures to characterize the interface bonding strength. Tensile tests are performed on T-shaped specimens with different cross-sectional areas, and one of the shapes is used for subsequent testing. The fracture morphology of the T-shape samples presented obvious dimples and cleavage steps at the fracture, indicating that the fracture mechanism is hybrid fracture. When the laser power is 2200 W, the T-shaped sample has a higher interface bonding strength of 637 MPa. The effectiveness and repeatability of the method are proved by comparative experiments. This study provides new insights into the better evaluation of laser cladding interface bonding strength in engineering applications.